De novo transcriptome assembly and functional analysis reveal a dihydrochalcone 3-hydroxylase(DHC3H) of wild Malus species that produces sieboldin in vivo - Miranda, Simón; Lagrèze, Jorge; Knoll, Anne-Sophie; Angeli, Andrea; Espley, Richard V.; Dare, Andrew P.; Malnoy, Mickael; Martens, Stefan (Frontiers in Plant Science, 2022)
Sieboldin is a specialised secondary metabolite of the group of dihydrochalcones (DHC), found in high concentrations only in some wild Malus species, closely related to the domesticated apple (Malus x domestica L.). To date, the first committed step towards the biosynthesis of sieboldin remains unknown. In this study, we combined transcriptomic analysis and a de novo transcriptome assembly to identify two putative 3-hydroxylases in two wild Malus species (Malus toringo (K. Koch) Carriere syn. sieboldii Rehder, Malus micromalus Makino) whose DHC profile is dominated by sieboldin. We assessed the in vivo activity of putative candidates to produce 3-hydroxyphloretin and sieboldin by de novo production in Saccharomyces cerevisiae. We found that CYP98A proteins of wild Malus accessions (CYP98A195, M. toringo and CYP98A196, M. micromalus) were able to produce 3-hydroxyphloretin, ultimately leading to sieboldin accumulation by co-expression with PGT2. CYP98A197-198 genes of M. x domestica, however, were unable to hydroxylate phloretin in vivo. CYP98A195-196 proteins exerting 3-hydroxylase activity co-localised with an endoplasmic reticulum marker. CYP98A protein model from wild accessions showed mutations in key residues close to the ligand pocket predicted using phloretin for protein docking modelling. These mutations are located within known substrate recognition sites of cytochrome P450s, which could explain the acceptance of phloretin in CYP98A protein of wild accessions. Screening a Malus germplasm collection by HRM marker analysis for CYP98A genes identified three clusters that correspond to the alleles of domesticated and wild species. Moreover, CYP98A isoforms identified in M. toringo and M. micromalus correlate with the accumulation of sieboldin in other wild and hybrid Malus genotypes. Taken together, we provide the first evidence of an enzyme producing sieboldin in vivo that could be involved in the key hydroxylation step towards the synthesis of sieboldin in Malus species.